Best Filipino stories the NVM Gonzalez Awards, 2000-2005 - Abad, Gemino Henson 1939-; Brillantes, Gregorio C. 1932- (University of the Philippines Press, 2007)
"Here are seventeen of the best short stories in English over the first six years of the NVM Gonzalez Awards (2000 to 2005)... All these stories are, says Gregorio C. Brillantes in his splendid Preface, "astonishingly varied in vision, voice, mode, manner and consummation,... each a vivid dream sustained by language; every one a shining performance." All are eminently worthy of N.V.M. Gonzalez whom the Awards honor and memorialize because all "display," as Brillantes says, "the munificent range of the Filipino imagination, its manifold secrets, discoveries and conglomerations."--Back cover.